Design and practice of innovative practice workshop for new nurses based on creativity component theory and outcome based education(OBE) concept - Yang, Hao; Zhu, Hui; Luo, Wanying; Peng, Wentao (BMC medical education, 2023)
Objective To design a teaching model of innovative nursing practice workshop for new nurses based on creativity component theory and OBE concept, and to explore its implementation effect and application evaluation. Methods Using convenience sampling, 50 newly recruited nurses in 2021 from a tertiary hospital in Chengdu were selected as the study subjects and taught using the new nurses’ innovative practice workshop based on creativity component theory and the OBE concept. Results Before and after the implementation of the teaching, the new nurses’ creativity scale scores were significantly improved, and the effects of practice demonstration, teaching satisfaction results, and research output (one-year follow-up) were better. All 50 new nurses (100%) expressed willingness to participate in the course again. Conclusions Based on creativity component theory and the OBE concept, the innovative practice workshop for new nurses integrates theory and practice, and fully mobilizes students’ thinking, interest, and subjective initiative; during the teaching process, students’ creative thinking and problem-solving skills are improved, in addition, teamwork, literature review, communication and other skills are improved to different degrees, which is conducive to the research results. In addition, students’ abilities in teamwork, literature review, communication, and other aspects have been improved to different degrees, which is conducive to producing scientific research results and lays a good foundation for their future career development. No patient or public contribution No patient or public contribution is involved in this study.